2005
DOI: 10.1158/1055-9965.epi-05-0173
|View full text |Cite
|
Sign up to set email alerts
|

Improving Organochlorine Biomarker Models for Cancer Research

Abstract: Multivariate methods were used to predict levels of dichlorodiphenyldichloroethene (DDE) and polychlorinated biphenyl (PCB) concentrations in plasma from characteristics that included age, diet, race, reproductive history, socioeconomic status, and reported body mass index (BMI) at several decades of life before blood collection. Measurements were available for organochlorine compound (organochlorines), cholesterol, and triglycerides in plasma from 1,008 women participants in a population-based case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
80
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 55 publications
(67 reference statements)
12
80
1
2
Order By: Relevance
“…Examination of the relationships between 2004 serum PCB concentrations and demographic variables provides additional insights, as well as confirming that the results reported here are similar to those found in previous studies. Current serum PCB concentrations were significantly and positively associated with the age of the individual, a finding that has been previously reported (Wolff et al, 2005). There were also significant gender differences in current serum lipid-adjusted PCB concentrations, with men in our cohort having higher serum PCB concentrations than women.…”
supporting
confidence: 88%
“…Examination of the relationships between 2004 serum PCB concentrations and demographic variables provides additional insights, as well as confirming that the results reported here are similar to those found in previous studies. Current serum PCB concentrations were significantly and positively associated with the age of the individual, a finding that has been previously reported (Wolff et al, 2005). There were also significant gender differences in current serum lipid-adjusted PCB concentrations, with men in our cohort having higher serum PCB concentrations than women.…”
supporting
confidence: 88%
“…For example, in two breast cancer cohorts of older women (ref. 8 and unpublished data from ref. 15), both DDE and PCB were positively associated with BMI, but negatively associated with weight gain in multivariate linear regression models.…”
Section: Assessing Pharmacokinetic Variability In Statistical Modelsmentioning
confidence: 94%
“…In Fig. 2, intensity was derived from reported levels of dietary and ambient DDT contamination in the United States, which peaked around 1965 (8). During a long interval of exposure involving uptake and elimination, weight gain will differ for each birth cohort, and this will alter correlations of HHC with BMI at the time of HHC measurement for different cohorts.…”
Section: Assessing Pharmacokinetic Variability In Statistical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, if the effect of DDT exposure early in life on breast cancer risk is large [a possibility suggested by Cohn et al (2007)], then the decreasing birth cohort trend in breast cancer risk that has been observed for U.S. baby boomers is even more remarkable (Chu et al 1999; Tarone 2006, 2007; Tarone and Chu 2000). Women born after 1945 would have been exposed to DDT for each of the first 13 years of life, with increasing exposure through the late 1960s (Wolff et al 2005), but the birth cohort risk of breast cancer showed a marked decrease among U.S. women for over two decades after 1945. DDT exposure would join a list of other breast cancer risk factors predicting increasing breast cancer risk in baby boomers (Tarone 2006); yet the birth cohort risk of breast cancer decreased for women born after 1945.…”
mentioning
confidence: 99%